THE EFFECTIVENESS OF EARLY MOBIL EFEKTIFITAS MOBILISASI DINI TERHADAP KEKUATAN OTOT DAN SKALA NYERI PADA PASIEN POST ORIF FRAKTUR TIBIA FIBULA DI RUMAH SAKIT DI JAKARTA PUSAT - Erwan Setiyono; Yani Sofiani; Ninik Yunitri; Nurma Dewi (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Fracture is a condition where there is a break in bone tissue. ORIF is a surgical procedure that aims to restore the condition of the fracture as before. The problems that arise after ORIF is the occurrence of pain and limited activity. To reduce the problems that arise is to implement ROM (Range Of Motion) early mobilization. ObjectiveROM is to increase muscle strength and reduce the pain scale experienced by patients with tibia and fibula fractures. The method in this study was quasi-experimental with the total sampling technique. The analysis in this study used the Jamovi application with the Paired Samples T-Test and Repeated Measurement ANOVA. After ROM training there was a significant increase (P-value = <0.001) during the 4 days of hospitalization with a mean difference ranging from 2.00. In early mobilization exercises carried out independently at home for 10 days there was a significant increase in muscle strength (P-value = <0.001) with a mean difference ranging from 3.40. In measuring the pain scale after the ROM intervention was carried out for 4 days in the hospital, the results showed a significant decrease (P-Value = <0.001) with a mean difference of around -2.00. Meanwhile, in measuring the pain scale on days 7 and 14 of independent ROM exercises at home, the results were not significant where the P-value = 0.363 with a difference in mean values ​​ranging from +0.100. The application of EBNP, namely the provision of early mobilization exercises (ROM) has proven effective in increasing muscle strength and gradually reducing the pain scale in patients with tibia and fibula fractures.